Low-temperature thermally modified fir-derived biomorphic C–SiC composites prepared by sol-gel infiltration. Issue 6 (15th March 2023) - Li, Guo-Qing; Yu, Min; Luo, Hang; Huang, Ze-Ya; Fu, Ren-Li; Gucci, Francesco; Saunders, Theo; Zhu, Kong-Jun; Zhang, Dou
Abstract: In order to solve the problems (i.e. low infiltration efficiency, cracks, interface separation and poor mechanical properties) in the process of wood-derived C–SiC composites, the thermal modification of fir at low temperatures (300 °C ∼ 350 °C) combined with sol-gel infiltration was used to successfully produce biomorphic ceramics. The prepared materials were comprehensively characterized and exhibited improved interfacial bonding between C and SiC and mechanical properties. The weight gain per unit volume (0.123 g/cm 3 ) of SiO2 gel in the fir thermally modified at 300 °C is 167.4%, higher than that (0.046 g/cm 3 ) of the unmodified fir. A well-bonded interface was formed between the SiO2 gel and the pore wall of the fir thermally modified at 300 °C. With the increase of modification temperature from 300 °C to 350 °C, the distance between SiO2 gel and the pore wall increases, and a gap (1–3 μm) is observed between SiO2 gel and the pore wall of the fir carbonized at 600 °C. The C–SiC composites sintered at 1400 °C exhibited the highest compressive strength and bending strength of 40.8 ± 5.8 MPa and 11.7 ± 2.1 MPa, respectively, owing to the well-bonded interface between C of fir thermally modified at 300 °C and SiC. However, the composites sintered at 1600 °C for 120 min exhibited the lowest compressive strength and bending strength of 28.1 ± 13.4 MPa and 5.7 ± 1.6 MPa, respectively, which are 31.1% and 51.3% lower than those sintered at 1400 °C for 120 min, respectively. This might result from the porous structure formed by the excessive consumption of fir-derived carbon during the reaction between C and SiO2 at 1600 °C for 120 min. Therefore, thermal modification in the preparation of biomorphic C–SiC composites can promote slurry infiltration and the formation of a well-bonded interface between C and SiC, thus improving the mechanical properties of the composites.